Dynamics of blood indicators as a marker of the grain of the grease peritonitis - Savytskyi, I. V.; Znamerovskyi, S. G.; Koshelnik, O. L.; Miastkivska, I. V.; Grigoriev, P. E.; Yakimchuk, N. V. (Journal of Education, Health and Sport, 2017)
Introduction. Bile peritonitis is one of the most serious diseases of the abdominal cavity. The severity of its course and the percentage of mortality is primarily depends on endogenous intoxication. Therefore, effective sanitation of the abdominal cavity is an important element of the complex treatment of this pathology. Goal. Study of the dynamics of hematological parameters in the development of experimental bile peritonitis. Materials and methods of research. The investigation was carried out on 180 rats of the Wistar line with a mass 180-200 grams. Animals were divided into 4 groups: 1 group - intact (20 animals); 2 group - control - rats, that were modeled bile peritonitis without further correction (80 animals); Group 3 - animals whose modeled bile peritonitis was corrected by ablation of the abdominal cavity with a solution of furacilin and standard antibiotic therapy (40 animals); 4 group - rats, whose modeled bile peritonitis was corrected according to the combined scheme of detoxification. The task of this work is to investigate the dynamics of the indicators on the 1st, 3rd and 7th days. Results. The choice of erythrocyte, hemoglobin, hematocrit, ESR, leukocyte and leukocyte index of intoxication is optimal for the analysis of pathophysiological aspects of experimental bile peritonitis. Very high differences (p <0.001) between 1 and 3 days were revealed in the analysis of all markers in the 2nd group. Rats of this group who did not receive any therapy did not survive until the 7th day. Differences between the indices on the 1st, 3rd and 7th days at the level of statistical significance p<0.001 were revealed: in the analysis of hemoglobin in the 3rd group; hematocrit in the 3rd and 4th groups; leukocytes in the 4th group; LII in the 3 rd and 4 th groups; ESR in the 3rd and 4th groups. In the study of hemoglobin in the 4th group and hematocrit in the 1st group it was revealed that the differences between the 1st and 3rd, and also the 1st and 7th days were very high (p <0.001). Between the 3rd and the 7th day the indicators were at the level of significance p <0.01. Also, there were different group indicators (p <0.001): between 1st and 3rd, 1st and 7th days. However, there are no differences between the 3 rd and 7 th days. This indicates that the change in the indicator, which was formed on the 3rd day, is preserved without statistically significant dynamics until the 7th day. Such changes are characteristic for the dynamics of the level of erythrocytes in the 4th group, and for changes in the level of leukocytes in the 1 st group. In the group of intact animals, during the studying of hemoglobin and ESR values, differences were found at the level of p <0.01 between the indices obtained on the 1st and 7th day of the experiment. The absence of changes throughout the experiment is typical for the following indicators in the groups: in the 1st group during the analyzing of number of red blood cells and LII; in the second group - in the analysis of hemoglobin, LII and the number of leukocytes. Conclusions. Conducting blood sampling on the 1st, 3rd and 7th day with the conditions of our experiment allows us to fully reveal the features of the flow of experimental bile peritonitis, as well as the influence of the methods of its correction in dynamics.